2011
DOI: 10.1590/s1679-45082011ao2081
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration and ethanol sclerotherapy to treat recurrent ovarian endometriomas prior to in vitro fertilization – a pilot study

Abstract: Objective: To describe the evolution of controlled ovarian hyperstimulation in women with recurrent ovarian endometriomas treated with sclerotherapy. Methods: Twenty-one patients with a laparoscopic diagnosis of stage III or IV endometriosis who had an endometrioma larger than 3 cm before ovarian hyperstimulation for in vitro fertilization were included in the study. After using a GnRH agonist analog for at least 20 days, the cysts were punctured using ultrasound guidance and subsequent ethanol sclerotherapy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 30 publications
1
20
0
1
Order By: Relevance
“…Finally, therefore, 18 studies were included in the present review. Supplemental Tables 1 and 2 show study characteristics and risk of bias (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Literature Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, therefore, 18 studies were included in the present review. Supplemental Tables 1 and 2 show study characteristics and risk of bias (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Literature Identificationmentioning
confidence: 99%
“…Sclerotherapy was performed transvaginally (13 studies), transabdominally (one study), or both (three studies). In women who were treated with the use of ethanol sclerotherapy, 11 studies used the ethanol ''washing'' technique (ethanol was instilled for 0-15 minutes and then removed) (13,15,16, 20, 21 24, 26, 28, 29), and in four studies the ethanol was left in situ (14,17,19,22). The volume of ethanol instillation ranged from 50% to 100% of the initial aspirated cyst volume.…”
Section: Reported Interventions During Endometrioma Sclerotherapymentioning
confidence: 99%
“…It has been shown previously that a larger cyst diameter is significantly associated with recurrence (31) and that women with cyst size ≤ 5 cm experience a higher recovery rate (23). Additionally, Andre and colleagues stated that ovarian cysts with a mean diameter of 4.7 cm did not recur after aspiration (26). It is confirmed that larger cysts have thick multiple septa and several cavities and hold more pathologic fillings; therefore, a larger area of endothelial lining is involved during the manipulation of these cysts.…”
Section: Discussionmentioning
confidence: 97%
“…Ethanol sclerotherapy is a good alternative policy to avoid detrimental effects of laparoscopic cystectomy on ovarian function (18,25). Andre and colleagues et al reported a 20% pregnancy rate after ethanol sclerotherapy of ovarian endometrioma subsequent to ovarian stimulation with GnRh agonist protocol (26). In our previous clinical trial, we enrolled 40 women with recurrent endometrioma for an IVF cycle; 20 patients randomly underwent International Journal of Reproductive BioMedicine Ethanol sclerotherapy and endometrioma ethanol sclerotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies, and the results are contradictory. Some studies demonstrated a benefit [ 20 , 22 , 29 31 ], whereas others did not show any significant improvement. Currently, the role of EST in the management of endometriomas is not well defined as demonstrated by the meta-analysis of Cohen et al [ 19 ].…”
Section: Introductionmentioning
confidence: 99%